Comprehensive Analysis of Business Strategies and Adaptive Innovation in Responding to Changes in Consumer Consumption Patterns During the New Year Moment - Judijanto, Loso; Az Zaakiyyah, Hizbul Khootimah; Jusman, Ikhsan Amar (ADMAN: Journal of Contemporary Administration and Management, 2024)
This study aims to comprehensively analyze business strategies and adaptive innovations in responding to changes in consumer consumption patterns during the New Year period. Using a literature review method and a qualitative approach, data was gathered from Google Scholar for the period 2020-2024. Out of 30 articles found, 19 relevant articles were selected through a strict selection process. Descriptive analysis was used to identify trends, patterns, and adaptive strategies applied by business actors, especially SMEs. The results show that effective business strategies involve product innovation, the use of digital technologies, local cultural-based approaches, and cross-sector collaboration. Additionally, the integration of sustainability values becomes an essential element in creating long-term competitiveness. Relevant case studies, such as Tokopedia's promotional programs and Maison Weiner's product innovations, highlight how adaptive strategies can be effectively implemented. This research provides practical implications for business practitioners and government policies, as well as offering theoretical contributions to the literature on business strategies based on adaptive innovation.